2015
DOI: 10.1021/acs.joc.5b02318
|View full text |Cite
|
Sign up to set email alerts
|

First Total Synthesis of Gliomasolide C and Formal Total Synthesis of Sch-725674

Abstract: Syntheses of two 14-membered macrolides Sch-725674 and Gliomasolide C are described here. The first total synthesis of Gliomasolide C, the short synthesis of Sch-725674, and regioselective Wacker oxidation of internal olefin are the highlights of this disclosure. In addition, a key macrocycle with orthogonal functionalities was designed and synthesized on a gram scale for the generation of analogues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…220 Denrodolides C and D (Dendrodochium sp., sea cucumber Holothuria nobilis) have been prepared from commercially available materials. 221 The macrolide gliomasolide C (Gliomastix sp., sponge Phakellia fusca) has been synthesised, 222 as has the lipopeptide fellutamide A (Penicillium fellutanum, sh Apogon endekataenia) 223 and the alkaloids penipanoid C and 2-(4hydroxybenzyl)quinazolin-4(3H)-one (Penicillium paneum, sediment). 224 A number of new activities were reported for known fungal metabolites.…”
Section: Marine-sourced Bacteriamentioning
confidence: 99%
“…220 Denrodolides C and D (Dendrodochium sp., sea cucumber Holothuria nobilis) have been prepared from commercially available materials. 221 The macrolide gliomasolide C (Gliomastix sp., sponge Phakellia fusca) has been synthesised, 222 as has the lipopeptide fellutamide A (Penicillium fellutanum, sh Apogon endekataenia) 223 and the alkaloids penipanoid C and 2-(4hydroxybenzyl)quinazolin-4(3H)-one (Penicillium paneum, sediment). 224 A number of new activities were reported for known fungal metabolites.…”
Section: Marine-sourced Bacteriamentioning
confidence: 99%
“…egy. [5] A few more total syntheses of the same macrolactone were reported by Prasad et al [6] and Kaliappan et al [7] During the preparation of our manuscript, Reddy et al [8] reported the formal total synthesis of Sch725674 (1).…”
Section: Introductionmentioning
confidence: 67%
“…Higher catalyst loading of G-I (up to 10 mol%) did not improve the yield. To enhance the yield of macrocycle product, next we conducted the RCM 13 reaction of diene 8 under G-II conditions at reflux for 12 hours to furnish 21 with an E-olefinic bond (J = 15.8 Hz) in 65% yield. Finally, the deprotection of MOM groups on exposure to 6 N HCl afforded the target compound 1 in 88% yield.…”
Section: Syn Thesismentioning
confidence: 99%
“…6 In summary, we have accomplished the stereoselective total synthesis of pestalotioprolide C (1) in 13 linear steps by invoking Keck allylation, Sharpless kinetic resolution, and ring-closing metathesis as key steps in an overall yield of 4%. 1 H NMR spectra were recorded at 300/400/ 500 MHz, as specified, 13 C NMR spectra were recorded at 100 or 125 MHz, as specified. 1 H and 13 C NMR spectra were obtained from CDCl 3 or CD 3 OD as solvent.…”
Section: Syn Thesismentioning
confidence: 99%